Wits Architecture Student Works 1922-1980. Tomaselli, U R. Church, scale working drawings. BArch III 1937; Space & Structure. BArch V 1939 - Tomaselli, U R (My University, 2014)
Wits Architecture Student Works 1922-1980. Tomaselli, U R. Church, scale working drawings. BArch III 1937; Space & Structure. BArch V 1939
Wits Architecture Student Works 1922-1980. Tomaselli, U R. Church, scale working drawings. BArch III 1937; Space & Structure. BArch V 1939
Keywords: Wits Architecture Student Works 1922-1980. Tomaselli, U R. Church, scale working drawings. BArch III 1937; Space & Structure. BArch V 1939